Adult Education and Multirreferential Learning Environments - Casnati, Ana María (Advances in Social Sciences Research Journal, 2018)
The research presented here is developed in a multireferential learning environment corresponding to the Youth and Adult Education Space (ANEP CODICEN) in Tacuarembó. The objective is to know the reality and the context of the people who attend these Spaces to contribute to the improvement of their quality of life, enhancing their personal and professional development, using telematic mediation. Also understand the reasons why adults decide to become literate, research and systematize about the interests and needs of adults regarding educational activities involving ICTs and contribute to knowledge in the area of adult education in Uruguay. To do this, a survey of data on the Spaces in the country and action research in Adult Education Spaces in Tacuarembó is carried out, using a qualitative-quantitative methodological approach. This allows characterizing the program assistants using participant observation, semi-structured interviews and life histories. It is verified that socialization and learning is the main motivation for the concurrence to these Spaces. In the interior of the country the classes have a profile of primary education while in Montevideo they work with a modality of manual and / or play activities. The profile of the teacher influences the pedagogical proposals but the assessment of the attendees is positive since many students after having passed the exams exam decide to continue the learning process.